A novel Pb-poly aminophenol glassy carbon electrode for determination of tetracycline by adsorptive differential pulse cathodic stripping voltammetry. (10th February 2017) - Rajab Dizavandi, Zeinab; Aliakbar, Alireza; Sheykhan, Mehdi
Graphical abstract: Highlights: The new introduced Pb-polymeric electrode is stable during repetitive analysis. The renewing of electrode surface is not necessary. The fabricated electrode has high hydrogen overvoltage. Self accumulation of tetracycline on this electrode eliminates many interferences. Wide range linearity and low LOQ. Abstract: A novel type of Pb-polyaminophenol filmed glassy carbon electrode for adsorptive cathodic stripping analysis of trace amounts of tetracycline was developed. The Pb-polymer electrode was fabricated in situ by simultaneous electrodeposition of Pb and cathodic electropolymerization of 4-nitrophenol in a sodium acetate medium at −1.5 volt. The prepared Pb-polymeric film was characterized by CV, FT-IR (ATR), H-NMR, SEM, EDS and a suitable mechanism for the electrode-reaction was proposed. The outputs of some experiments showed that tetracycline can be adsorbed on the surface of this Pb-polymer filmed electrode in an open circuit condition. Therefore it was used in adsorptive cathodic stripping analysis of tetracycline. The response of the electrode was enhanced in the presence of cetyltrimethylammonium bromide. Some parameters affecting the performance of the electrode were studied and optimized. The response of the electrode was linear in the range of 5 × 10 −8  − 1 × 10 −5  mol L −1 of tetracycline with a correlation coefficient of 0.9981. The relative standard deviation for 5 × 10 −7  mol L −1 of tetracycline was 1.8% (n = 5). The L.O.D and L.O.Q were 4 × 10 −9 and 1.3 × 10 −8  mol L −1 of tetracycline, respectively. The introduced electrode was used for determination of tetracycline residues in some samples and the obtained results were in good agreement with the results of HPLC.